Environmental chemicals and DNA methylation in adults: a systematic review of the epidemiologic evidence. - Ruiz-Hernandez, Adrian.; Kuo, Chin-Chi.; Rentero-Garrido, Pilar.; Tang, Wan-Yee.; Redon, Josep.; Ordovas, Jose M.; Navas-Acien, Ana.; Tellez-Plaza, Maria. (2016)
Abstract: Current evidence supports the notion that environmental exposures are associated with DNA-methylation and expression changes that can impact human health. Our objective was to conduct a systematic review of epidemiologic studies evaluating the association between environmental chemicals with DNA methylation levels in adults. After excluding arsenic, recently evaluated in a systematic review, we identified a total of 17 articles (6 on cadmium, 4 on lead, 2 on mercury, 1 on nickel, 1 on antimony, 1 on tungsten, 5 on persistent organic pollutants and perfluorinated compounds, 1 on bisphenol A, and 3 on polycyclic aromatic hydrocarbons). The selected articles reported quantitative methods to determine DNA methylation including immunocolorimetric assays for total content of genomic DNA methylation, and microarray technologies, methylation-specific quantitative PCR, Luminometric Methylation Assay (LUMA), and bisulfite pyrosequencing for DNA methylation content of genomic sites such as gene promoters, LINE-1, Alu elements, and others. Considering consistency, temporality, strength, dose-response relationship, and biological plausibility, we concluded that the current evidence is not sufficient to provide inference because differences across studies and limited samples sizes make it difficult to compare across studies and to evaluate sources of heterogeneity. Important questions for future research include the need for larger and longitudinal studies, the validation of findings, and the systematic evaluation of the dose-response relationships. Future studies should also consider the evaluation of epigenetic marks recently in the research spotlight such as DNA hydroxymethylation and the role of underlying genetic variants.; Keywords: Systematic review, DNA methylation, Environmental chemicals, Cadmium, Lead, Mercury, Metals, Persistent organic pollutants, Bisphenol A, Polycyclic aromatic hydrocarbons.; Springer Open.